BANTUAN HUKUM TERHADAP TERSANGKA YANG DIANCAM PIDANA LIMA TAHUN ATAU LEBIH DALAM PROSES PENYIDIKAN - sunaryo sunaryo (JURNAL AKTA YUDISIA, 2020)
Abstract Sunaryo. 2019. Legal Assistance to Suspects who are subject to a sentence of five years or more in The Investigation Process. Under supervised by Dr. Syafruddin, S.H., M.Hum, Dr. Ilham Agang, S.H., M.H                     This research background was based on the law enforcement of criminal law in Indonesia where the appreciation of human rights is often ignored by investigators to the suspect by doing acts of violence both psychological and physical violence through persecution. This occurred because suspects do not have legal assistance in process investigation.  Based on Criminal Code Procedures (KUHAP) guarantees the right of suspects who threatened with a sentence of five years or more must be accompanied by his/her lawyer at every level of examination as stipulated in Article 114 KUHAP in section Article 56, verse (1). The research design of this research was normative law. The statute approach and conceptual approach were used in analyzing research data. Research data were primary; written law product, and secondary; law literature and specific literature and other relevant research sources. The results showed that the fulfillment of legal assistance to the suspects, who were threatened with a sentence of five years or more, in the investigation process was necessary needed to protect their rights and avoid acts of arrogance, arbitrariness, physical acts and psychological violence. However, if the investigators do not fulfill this matter, the lawsuits or demands of the public prosecutor cannot be accepted, so the case file is returned and asked for reinvestigation is carried out in accordance with the Criminal Procedure Code. The investigators should be punished because of their negligence. This research recommends that investigators should carry out the process investigations adhere to the Criminal Procedure Code by providing legal assistance to the suspect and if investigators commit negligence in carrying out investigations can be prosecuted with the ethics code of the National Police based on the law criminal procedure. Keywords: Legal assistance, Sanctions, and suspect's rights